Peak Oxygen Uptake Recovery Delay After Maximal Exercise in Patients With Heart Failure. Issue 6 (November 2020) - Kadariya, Dinesh; Canada, Justin M.; Del Buono, Marco Giuseppe; van Wezenbeek, Jessie; Tchoukina, Inna; Arena, Ross; Van Tassell, Benjamin; Abbate, Antonio
Abstract : Purpose: Peak oxygen uptake recovery delay (V˙o2 peakRD), measured as the time until post-exercise oxygen uptake (V˙o2 ) decreases below V˙o2 peak following maximal cardiopulmonary exercise testing (CPX), has been recognized as an abnormal response, associated with reduced cardiac output reserve during exercise in patients with heart failure (HF). In the current study we examined the association of V˙o2 peakRD during routine CPX testing of patients with symptomatic HF across a wide range of left ventricular ejection fraction (LVEF) values with clinical biomarkers. Methods: In this retrospective study, 80 clinically stable symptomatic HF patients across a wide range of LVEF at our institution were evaluated that put forth a minimally acceptable effort during CPX testing (respiratory exchange ratio ≥ 1.00). The V˙o2 peakRD was measured in 10-sec intervals following maximal CPX testing. Markers of elevated cardiac filling pressures (N-terminal pro-brain natriuretic peptide [NTproBNP] and echocardio-Doppler E/e') and other key CPX parameters were explored for their association with V˙o2 peakRD. Results: The mean V˙o2 peakRD and V˙o2 peak were 10 (interquartile range 10, 40) sec and 13.9 (11.6, 16.4) mL· kg −1 · min −1, respectively. V˙o2 peakRD demonstrated a positive linear trend with serum NTproBNP levels and E/e' ( T JT = 1239.500, z = 2.634, P < .01; T JT = 1081.000, z = 2.046, P = .04, respectively). Conclusion: Prolonged V˙o2 peakRD following exercise is associated with markers of greater disease severity in patients with HF. Abstract : Peak oxygen consumption recovery delay (V˙o2 peak RD) is measured as the time until post-exercise oxygen consumption (V˙o2 ) decreases below V˙o2 peak RD following maximal cardiopulmonary exercise testing. Prolonged V˙o2 peak RDRD following exercise is associated with markers of greater disease severity in patients with heart failure.